Development of a Simplified Programming Kit Based 16LF18856 for Embedded Systems Testing and Education in Developing Countries - Nguimfack-Ndongmo, Jean de Dieu; Kentsa Zana, Kevin; Asoh, Derek Ajesam; Kengnou Telem, Nicole Adélaïde; Kuate-Fochie, René; Kenné, Godpromesse (Journal of electronic testing, 2022)
Embedded systems and applications have recently emerged as a domain of high interest to the general public in developing countries. Unfortunately, these countries lack the technological infrastructure for the design, testing, and implementation of projects in the domain. This paper presents a Very Simple Programming Kit (VSPK) for Embedded Systems suitable for practical training, project design, and testing in the domain for use in developing countries. The microcontroller-based system makes it easy to test, teach and train in various areas of embedded systems including programming, communication, signal acquisition and processing, remote control, and domotics. A VSPK prototype has been produced and is used for real-time simulation of Embedded applications. This operation involves the VSPK, the PIC programmer, the PC and the application program to be tested progressively and the displays observed on the LCD and LEDs. The debugging process is easily performed and errors are detected and corrected. The main features of VSPK are low production cost, low power consumption, flexible peripheral pin selection, integrated LCD module, and simple hardware and software environment. Unlike similar kits available for educational purposes, VSPK possesses some advantages such as an integrated graphic color LCD, a configurable internal oscillator, numerically controlled oscillators, testing LEDs, testing buttons, and complete access to multiple programming languages. Two experimental and simple tests for validation of VSPK have been carried out, and the results show that VSPK performs satisfactorily.